Jenkins CI/CD and Github in One Hour Video Course - Deza, Alfredo; Deza, Alfredo; Gift, Noah (Pragmatic AI Solutions, 2021)
Get started with Jenkins, Jenkins Pipelines, and Github integration in this introductory video to the most widely used CI/CD platform in the world: Jenkins. Learn how to setup an example repository from Github into Jenkins using the same techniques you would need to scale a massive CI CD production environment. Topics include: * Install and configure Jenkins including plugins like Blue Ocean that enables pipelines * Create a Personal Access Token (PAT) in Github to connect a repository to Jenkins * Setup a trigger to run automated tests for the Github repository using a Jenkinsfile * Add a remote node or slave to the Jenkins master instance via SSH to quickly scale up operations * Validate that the project builds and deploys correctly.